Risk factors for 30-day mortality in patients with cancer and COVID-19 in Turkey: A single center retrospective study - Mutlu, Emel; Firat, Sedat Tarik; Inanc, Mevlude; Bozkurt, Oktay; Cosar, Ramazan; Ozkan, Metin (Annals of Medical Research, 2022)
Aim: We aimed to investigate the factors affecting mortality in cancer patients with COVID-19. Materials and Methods: 120 cancer patients followed-up in Erciyes University Medical Oncology Department were included in the study. Patients with a diagnosed cancer over the age of 18 years and diagnosis of COVID-19 between April 1 and December 1 2020 were participated in the study. The relationship between clinical, demographic, laboratory values and 30-day mortality were evaluated using the Chi-square and Fisher's exact test. Risk factors for mortality were identified by univariable and multivariable logistic regression models. Results: 120 cancer patients were accepted in the study and 30 (25%) had died within 30 days after COVID-19 positivity. Hospitalization rate of cancer patients with COVID-19 was 67.5% and 23 (19.2%) of patients were admitted to intensive care unit (ICU). 34.6% of hospitalized patients and 95.7% of those admitted in the ICU died within 30 days. In multivariable logistic regression analysis, it was concluded that the presence of lymphopenia (OR 2.2, 95% CI 1.54-13.6, p = 0.04), high neutrophil-lymphocyte ratio (NLR) (OR 3.1, 95% CI 1.21-9.8, p = 0.02), dyspnea (OR 2.5 95% CI 0.32-11.2, p = 0.04), lung cancer diagnoses (OR 3.3 95% CI 1.54-9.7, p = 0.03), male gender (OR 2.17 95% CI 1.1-7.3, p = 0.03) ) were determined that increased 30-day mortality. Conclusion: High incidence of cancer and the risk of immunosuppression in these patients increased the importance of COVID-19. Cancer patients with COVID-19 need to be treated more carefully because they are vulnerable to infection and can be mortal.
Keywords: COVID-19; cancer; neutrophil lymphocyte ratio; pandemia